THE VERB “HIT” IN PALEMBANG LANGUAGE: NATURAL SEMANTIC METALANGUAGE STUDY - Jeni Arasyita Tazami; Agus Subiyanto (Universitas Islam Sumatera Utara (UISU), 2022)
Verb is one of the major lexical classes in language. There are three types of verbs, one of which is action verb, as found in the verb ‘hit’. The verb